2008
DOI: 10.1093/ndtplus/sfn120
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis catheter placement technique and complications

Abstract: Background. This review describes the peritoneal dialysis (PD) catheter implantation techniques for the treatment of PD. The PD catheter-related complications still cause significant morbidity and mortality, resulting in the necessity to switch to haemodialysis (HD) treatment.Methods. Several catheter insertion techniques, using an open surgical approach, laparoscopic and percutaneous techniques have been employed, with their specific early and late complications and failure rates.Results. Despite the similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 21 publications
(16 reference statements)
1
125
1
6
Order By: Relevance
“…Early complications included leakage, catheter dysfunction, hemoperitoneum, while late complications are defined by hernias, pleuroperitoneal leaks and sleeve externalization [9]- [11].…”
Section: Discussionmentioning
confidence: 99%
“…Early complications included leakage, catheter dysfunction, hemoperitoneum, while late complications are defined by hernias, pleuroperitoneal leaks and sleeve externalization [9]- [11].…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset complications include exit site leak, catheter malposition, hemoperitoneum, right-sided hydrothorax and ultrafiltration failure (UFF). The late-onset complications include abdominal hernia, scrotal swelling, encapsulated peritonitis and catheter cuff protrusion 5 . In this study, 30.8% patient fell pain during dialysis, because patient also may describe the pain which was related to other abdominal causes.…”
Section: Resultsmentioning
confidence: 99%
“…Among these techniques laparoscopic peritoneal dialysis catheter insertion had been reported to be the method of choice with low visceral injury, bleeding, incisional hernia and catheter disfunction risks. [14,15] On the other hand various meta-analysis have shown that all insertion methods have been comparable and there were no significant differences among different methods. [16][17][18] Currently; laparoscopic insertion of the peritoneal dialysis catheter is prefered due to better evaluation of the intraabdominal region, catheter fixation capability and availability of adhesiolysis upon observation.…”
Section: Discussionmentioning
confidence: 99%